Kewarganegaraan dan Hak Asasi Manusia : Studi tentang Perlindungan Hukum bagi Orang tanpa Kewarganegaraan (Stateless Persons) - Ashfiya Nur Atqiya; Ahmad Muhammad Mustain Nasoha; Isnaini A sifa Rohmah; Ahmad Abdul Aji Setiawan; Davina Intan Nur Fadila (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study examines the legal protection for stateless persons within the framework of citizenship and human rights. The focus is on assessing the effectiveness of international legal frameworks and national policies in safeguarding the fundamental rights of individuals without citizenship. The research employs a qualitative analysis of key legal instruments, including the 1954 Convention Relating to the Status of Stateless Persons and the 1961 Convention on the Reduction of Statelessness, alongside case studies of policy implementation across various countries. The findings reveal that, despite a robust international legal framework, there are significant gaps in implementation and enforcement, leading to ongoing discrimination and human rights violations against stateless persons. The study recommends comprehensive policy reforms and enhanced international cooperation to improve legal protection for this vulnerable group.